2021
DOI: 10.1007/978-3-030-71711-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Pre-trained CNN Based Deep Features with Hand-Crafted Features and Patient Data for Skin Lesion Classification

Abstract: Skin cancer is a major public health problem, with millions newly diagnosed cases each year. Melanoma is the deadliest form of skin cancer, responsible for the most over 6500 deaths each year in the US, and the rates have been rising rapidly over years. Because of this, a lot of research is being done in automated image-based systems for skin lesion classification. In our paper we propose an automated melanoma and seborrheic keratosis recognition system, which is based on pre-trained deep network combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Several studies have indicated that embeddings extracted from deep convolutional neural networks (CNNs) are powerful for various visual recognition tasks [ 35 , 36 , 37 ]. Their outstanding performance as image representation learners grew the trend of utilizing them as optimized feature generators for skin lesion classification [ 38 , 39 , 40 , 41 , 42 , 43 ]. Our work, aligned with previous research evidence, explores the efficiency of the pretrained CNN, namely the VGG16 [ 44 ] as the starting point, for the generation of image embeddings in order to discriminate between cases of atypical MM and atypical SK.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have indicated that embeddings extracted from deep convolutional neural networks (CNNs) are powerful for various visual recognition tasks [ 35 , 36 , 37 ]. Their outstanding performance as image representation learners grew the trend of utilizing them as optimized feature generators for skin lesion classification [ 38 , 39 , 40 , 41 , 42 , 43 ]. Our work, aligned with previous research evidence, explores the efficiency of the pretrained CNN, namely the VGG16 [ 44 ] as the starting point, for the generation of image embeddings in order to discriminate between cases of atypical MM and atypical SK.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of automated techniques for skin lesion detection depends on the selection of relevant descriptive characteristics extracted from dermoscopy images [34].…”
Section: Image Feature Extractionmentioning
confidence: 99%
“…Deep learning methods instead forego hand-crafted features in favor of a deep hierarchy of data-driven features. In the domain of skin lesions, a common approach rests on CNN models with softmax output layers to detect disease [31]. Recent studies have proposed numerous advances to improve the classification accuracy of skin lesions.…”
Section: Related Workmentioning
confidence: 99%